2013
DOI: 10.4103/0019-5049.108555
|View full text |Cite
|
Sign up to set email alerts
|

Endotracheal intubation through the intubating laryngeal mask airway (LMA-Fastrach™): A randomized study of LMA- Fastrach™ wire-reinforced silicone endotracheal tube versus conventional polyvinyl chloride tracheal tube

Abstract: Context:A wire-reinforced silicone tube (LMA-Fastrach™ endotracheal tube) is specially designed for tracheal intubation using intubating laryngeal mask airway (ILMA). However, conventional polyvinyl chloride (PVC) tracheal tubes have also been used with ILMA to achieve tracheal intubation successfully.Aim:To evaluate the success of tracheal intubation using the LMA-Fastrach™ tracheal tube versus conventional PVC tracheal tube through ILMA.Settings and Design:Two hundred adult ASA physical status I/II patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…High incidence of oesophageal intubation was observed with ILMA tube in our study as also observed by Kundra et al [12,20] Higher success of intubation with ILMA was noted when least resistance is felt in reservoir bag, maximum chest expansion is seen and optimum end tidal carbon dioxide (ETCO2) is observed on monitor during maneuvering of ILMA. [12,14,17,21] The limitations of our study is, it lacked blinding and a small study group. Lack of visualization of position of ILMA and the exact reason for unsuccessful passage of tracheal tube was not clear with ILMA.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…High incidence of oesophageal intubation was observed with ILMA tube in our study as also observed by Kundra et al [12,20] Higher success of intubation with ILMA was noted when least resistance is felt in reservoir bag, maximum chest expansion is seen and optimum end tidal carbon dioxide (ETCO2) is observed on monitor during maneuvering of ILMA. [12,14,17,21] The limitations of our study is, it lacked blinding and a small study group. Lack of visualization of position of ILMA and the exact reason for unsuccessful passage of tracheal tube was not clear with ILMA.…”
Section: Discussionmentioning
confidence: 96%
“…Time for intubation was higher with conventional PVC ET tube as observed because of the stiffness of the tube. [12,14,21] Cost of normal single use conventional PVC (Portex ET tube) is around Rs.180 per tube. Cost incurred for purchasing reusable (multiple use) ILMA tube is Rs.3900, recommended for thirty uses costing Rs.130 per use, making ILMA tube economical than PVC tube.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown that silicon reinforced tracheal tubes are better than polyvinylchloride tubes for intubation through LMA CTrach ™ . [10][11][12][13] Lopez AM et al studied 21 patients in which 12 patients required 24 manoeuvres for getting the good laryngeal view with the standard technique of insertion. Each patient required between 1 and 4 manoeuvres on an average.…”
Section: Discussionmentioning
confidence: 99%
“…The mean number of attempts at intubation was also significantly lower with silicone wire reinforced tubes in these studies. 8,[10][11][12] When the angle of emergence of the polyvinyl chloride tracheal tubes from various manufactures had been compared by Brain and his colleagues, the Portex PVC tube had an angle of emergence of 50 o . The angle of emergence with a straight silicone tube was 36 o .…”
Section: Discussionmentioning
confidence: 99%